2016
DOI: 10.1039/c6ta03729a
|View full text |Cite
|
Sign up to set email alerts
|

In situ formation of NiO on Ni foam prepared with a novel leaven dough method as an outstanding electrocatalyst for oxygen evolution reactions

Abstract: A novel leaven dough method was developed to prepare three-dimensional Ni foams, upon which a thin NiO nanostructure was grown through thermal oxidation to form NiO/Ni foams as a highly efficient electrocatalyst for oxygen evolution reactions (OER).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
75
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 50 publications
0
75
0
2
Order By: Relevance
“…Encouraged by the advance of efficient mass transfer and abundant active sites from micro/nanostructures, hollow Co 3 O 4 microtube array has been fabricated by electrochemical self‐templating approach for catalyzing OER, HER, and overall water electrolysis with high activity due to high surface area, hierarchical porosity, and hollow structure ( Figure a) . NiO/Ni arrays owing to the 3D well‐connected Ni foam skeleton and the intact contact of the NiO/Ni domains have been produced through in situ thermal oxidation of Ni foam in air instead of using a large amount of liquid solvent, requiring current density of 10 mA cm −2 at a low overpotential (345 mV) and a low Tafel slope (53 mV per decade) in 1 m KOH electrolyte . Beyond transition metal (Co, Ni)‐based electrocatalysts, self‐supported Cu‐based nanowire arrays including Cu(OH) 2 , CuO, Cu 2 O, and CuO x in situ grown on Cu foil have been produced as active and robust OER electrocatalysts .…”
Section: Electrocatalyst Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraged by the advance of efficient mass transfer and abundant active sites from micro/nanostructures, hollow Co 3 O 4 microtube array has been fabricated by electrochemical self‐templating approach for catalyzing OER, HER, and overall water electrolysis with high activity due to high surface area, hierarchical porosity, and hollow structure ( Figure a) . NiO/Ni arrays owing to the 3D well‐connected Ni foam skeleton and the intact contact of the NiO/Ni domains have been produced through in situ thermal oxidation of Ni foam in air instead of using a large amount of liquid solvent, requiring current density of 10 mA cm −2 at a low overpotential (345 mV) and a low Tafel slope (53 mV per decade) in 1 m KOH electrolyte . Beyond transition metal (Co, Ni)‐based electrocatalysts, self‐supported Cu‐based nanowire arrays including Cu(OH) 2 , CuO, Cu 2 O, and CuO x in situ grown on Cu foil have been produced as active and robust OER electrocatalysts .…”
Section: Electrocatalyst Categoriesmentioning
confidence: 99%
“…a) Hollow Co 3 O 4 microtube array. Reproduced with permission . Copyright 2017, The Royal Society of Chemistry.…”
Section: Electrocatalyst Categoriesmentioning
confidence: 99%
“…For example, CeO x /Cu(111) is more active than Cu/CeO 2 (111) and Cu/ZnO(0001) surfaces for the water-gas shift reaction. [9] The great success of these single crystal based model catalysts thus encourages the development of practical inverse catalysts.Up to now, the methods of reverse micro-emulsions, [12][13][14] impregnation, [15][16][17][18] atomic layer deposition, [19] nanosphere lithography [20] and gas-induced surface segregation, [5,[21][22][23] have been explored for the preparation of actual oxide/metal inverse catalysts. Nevertheless, these methods often involve multi-step processing with high temperature treatment, resulting in complication for scale-up syntheses.…”
mentioning
confidence: 99%
“…Over the past few years, nicked‐based transition metal materials, such as NiO,, NiO@Ni foam, NiCo 2 O 4 , NiFe 2 O 4 , NiO@NiS, Ni−P, and Ni 2 P/rGO have been intensively studied for supercapacitors. All of these materials present common advantages, namely, low cost and toxicity, and relatively high specific capacitance, energy density, and power density ,,.…”
Section: Introductionmentioning
confidence: 99%
“…reported that the Co‐doped Ni 3 P 2 O 8 −Co 3 P 2 O 8 ⋅ 8H 2 O with a Ni/Co molar ratio of 8 : 2 displayed the best electrochemical properties, which were better than those of both Ni 3 P 2 O 8 and Co 3 P 2 O 8 ⋅ 8H 2 O. According to the equation E=(1/2) ⋅ C ⋅ (ΔV) 2 , the energy density of asymmetric supercapacitors can be enhanced by voltage or specific capacitance. The cell voltage of asymmetric supercapacitors depends on where positive and negative electrodes are working in separate potential windows .…”
Section: Introductionmentioning
confidence: 99%